O joy, O joy, the Hobby-Horse is Remembered - Schandl, Veronika (Hungarian Journal of English and American Studies, 2022)
Book review: Pikli, Natália. Shakespeare’s Hobby-Horse and Early Modern Popular Culture. New York: Routledge, 2021. 286 pages. ISBN 9780367514150. Hb. 160.00